Social Media Effect on Financial Behavior of Generation Z Women with Financial Literacy as a Moderating Variable - Andi Dewi Angreyani; Asniwati Asniwati; M. Zadly Syahdi (Entrepreneurship, Management, and Business Research Journal, 2026)
This study aims to analyze the influence of Social media on the financial behavior of Generation Z women, with financial literacy as a moderating variable. Social media has become one of the primary sources of financial information for Generation Z, while financial literacy plays a crucial role in helping individuals manage their finances rationally. The study employs a quantitative approach using a survey method involving 253 Generation Z women in Palopo City, selected through purposive sampling. Data were collected using an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 3. The results indicate that financial literacy has a positive and significant effect on financial behavior (β = 0.327; p < 0.05). Social media also has a positive and significant effect on financial behavior (β = 0.571; p < 0.05) and is the most dominant variable. However, financial literacy was not found to moderate the relationship between Social media and financial behavior (β = 0.063; p > 0.05). The research model explains 66.4% of the variation in the financial behavior of Generation Z women (R² = 0.664).